Suplementasi Maggot Black Soldier Fly (Hermetia illucens) Pada Pakan Terhadap Performa Produksi Dan Analisis Usaha Ayam Kampung Super Periode Finisher - Muhammad Nazar Fuddin, - (2021)
This study aims to determine the analysis of super native chicken farm business with BSF (Black Soldier Fly) maggot supplementation on feed on the production performance of super native chickens, including feed consumption, body weight gain and feed conversion. This study used 50 super male native chickens aged 4 weeks and adapted for 1 week then randomized into five treatments (P0, P1, P2, P3, and P4) with five replications and each replication consisting of two super native chickens. The concentration of BSF maggots in this study was divided into five treatments, including P0 (basal feed without BSF maggot), P1 (basal feed + 2.5% BSF maggot), P2 (basal feed + 5% BSF maggot), P3 (basal feed + 7.5% BSF maggot), and P4 (basal feed + 10% BSF maggot). The basal feed in this study consisted of corn, soybean meal, rice bran, and fish meal. The newly harvested maggot is then weighed to determine the dose for each treatment and mixed with the feed ration in fresh form. Super native chickens were treated at 5 weeks of age and reared until 9 weeks of age. Statistical data analysis was processed using One Way ANOVA and followed by post hoc Duncan. The results showed that the level of feed consumption was high in treatment P4, the highest body weight gain was in P4, the lowest feed conversion was in P1. Contribution margin analysis (CM) was used to determine the benefits of the treatment in this study. 2.5% BSF (P1) maggot supplementation is recommended to increase profits.